Uber in Exurbia: Peripheral Platformization, Post-Suburbanization and the Public–Private Ridehail Partnership in the Toronto City Region - Fabian Namberger (International Journal of Urban and Regional Research, 2024)
After their widespread legalization, ridehailing companies Uber and Lyft soon embarked on a new stage of their respective business models: the initiation of a wave of strategic partnerships with local and regional transit agencies across the North American continent. This article accounts for this trend by putting forward the concept of the public–private ridehail partnership (PPRP). It aims to render visible the PPRP as a variously contradictory attempt to splice Uber and Lyft's platform-based business models with the existing social and physical realities of North American post-suburban space. While conceived as a strategic response to pressing sub- and exurban problems such as low physical densities, widespread car centrism and extensive transit undersupply, the PPRP, as I argue, is neither able to adequately address these dilemmas nor to ultimately resolve them. Rather, the PPRP latches onto old—and sets in motion new—powerful dynamics of heightened uneven development and continued urban entrepreneurialism. Each of these two dynamics is explored through empirical analyses of two recent PPRPs in the Toronto city region: the Lyft–Metrolinx pilot carried out between July and December 2019; and Uber's ongoing partnership with the town of Innisfil, located about 80 km north of downtown Toronto.
Keywords: 300; Uber; public–private ridehail partnership; post-suburbanization; peripheral platformization; ridehailing; smart urbanism; infrastructure; Innisfil; Toronto